Anthropology of cultural transformation. - Zhao, Xudong, 1965- author.
1 online resource (viii, 196 pages).
Keywords: As the first of a two-volume set on the anthropology of cultural transformation, this book discusses the manifestations of cultural transformation in the modern world and explores the re-establishment of cultural consciousness. Anthropology in the 21st century is confronted with a worldview of cultural transformation based on communication, collision, and interaction among cultures around the globe. This two-volume set aims to reorient the role and function of anthropology by focusing on the reconstruction of knowledge and cultural consciousness in order to better imagine and realize the synergetic interaction between different cultures and civilizations. In this first volume, the author provides an overview of the key issues and stances of anthropology in the face of cultural transformation. The book examines the trend of social and cultural transformation in the modern world and in China. It analyzes how the technology of separation brought about by modernity shapes family function and education. As a promising solution to this predicament, the book elucidates the importance of cultural consciousness in resisting disasters and social syndromes. The title will appeal to anthropologists, students, and general readers interested in anthropology, sociology, and ethnography.